The Role of Educators in Enhancing Student Learning Motivation in The Digital Technology Era - Febriyoli Elfa; Juliana Batubara; Nurfarida Deliani (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Education in the digital technology era presents new challenges and opportunities for educators in enhancing student learning motivation. The advancement of information and communication technology allows unlimited access to various learning resources but can also lead to distractions and a decline in student motivation. This article aims to discuss the role of educators in enhancing student learning motivation in the digital technology era. This research uses a literature study method, using literature as the main data source to explore theories and concepts regarding the role of educators in enhancing student learning motivation. The results of this study indicate that the role of educators in enhancing student learning motivation in the digital technology era is crucial. First, educators must be able to integrate technology into the learning process. With the proper use of technology, learning becomes more engaging and relevant to students, which in turn can increase their motivation to learn. Second, educators need to choose appropriate teaching methods to help students better understand the material. The right methods will make students feel more motivated to engage in learning. Furthermore, educators must understand the characteristics of their students, including their uniqueness and background. This understanding allows educators to adjust their teaching approaches to be more effective in enhancing student learning motivation. Lastly, educators must create activities that actively engage students in the classroom. Interactive activities that involve students can make them more interested and enthusiastic about learning.